Modeling Personal Agency through Fiction: Insights from A Good Girl’s Guide to Murder - Dewi Suryanti; Muhammad Fadli; Retno Anggraini; Refdi Akmal (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
A Good Girl’s Guide to Murder, a young adult novel by Holly Jackson, presents a compelling narrative of mystery while offering extensive opportunities to explore social and psychological dynamics through its main character. This study investigates the potential of the novel as a pedagogical tool by bridging young adult fiction and learning theories; analyzing how the protagonist, Pippa Fitz-Amobi, embodies Albert Bandura’s social cognitive theory. The research proposes fresh insights into their integration. Through the examination of personal agency, this study reveals how Pip’s agency shapes her decision-making and resilience in navigating complex situations. The findings highlight the effectiveness of young adult literature in illustrating fundamental learning principles, offering a modeling personal agency for its young readers.